Critical materials for water electrolysers at the example of the energy transition in Germany. (11th February 2021) - Kiemel, Steffen; Smolinka, Tom; Lehner, Franz; Full, Johannes; Sauer, Alexander; Miehe, Robert
Summary: The present work aims to identify critical materials in water electrolysers with potential future supply constraints. The expected rise in demand for green hydrogen as well as the respective implications on material availability are assessed by conducting a case study for Germany. Furthermore, the recycling of end‐of‐life (EoL) electrolysers is evaluated concerning its potential in ensuring the sustainable supply of the considered materials. As critical materials bear the risk of raising production costs of electrolysers substantially, this article examines the readiness of this technology for industrialisation from a material perspective. Except for titanium, the indicators for each assessed material are scored with a moderate to high (platinum) or mostly high (iridium, scandium and yttrium) supply risk. Hence, the availability of these materials bears the risk of hampering the scale‐up of electrolysis capacity. Although conventional recycling pathways for platinum, iridium and titanium already exist, secondary material from EoL electrolysers will not reduce the dependence on primary resources significantly within the period under consideration—from 2020 until 2050. Notably, the materials identified as critical are used in PEM and high temperature electrolysis, whereas materials in alkaline electrolysis are not exposed to significant supply risks. Abstract : This article evaluates the criticality of five pivotal materials of the three electrolysis technologies AEL, PEMEL and HTEL under the consideration of predicted increasing demands of electrolysis capacity in a scenario analysis approach. Furthermore, the potential of recycling EoL‐electrolysers for ensuring the sustainable supply of the considered materials is assessed. System boundary for the forecast of electrolysis capacity is Germany.